The first indigenous species of the millipede genus Eurygyrus C.L. Koch, 1847 from the European mainland, with remarks on E. nicarius (Verhoeff, 1901) and E. euboeus (Verhoeff, 1901), and a key to the species of the genus (Diplopoda: Callipodida: Schizopetalidae) - Stoev, Pavel; Enghoff, Henrik (Zootaxa, 2004)
The genus Eurygyrus C.L. Koch, 1847 (Schizopetalidae) comprises 17 described species from Asia Minor and the Aegean islands, some of them the largest callipodidans in the world. Here, we describe E. peloponnesius sp. n., the first species from the Greek mainland, found in the Taygetos Mts. The holotypes of E. euboeus (Verhoeff, 1901) and E. nicarius (Verhoeff, 1901), both known only from females, are re-examined and are found both to be distinct from the new species. A key to all, but two species of Eurygyrus is included.